Novel approaches for the assessment of relative body weight and body fat in diagnosis and treatment of anorexia nervosa: A cross-sectional study. Issue 6 (December 2019) - Lackner, Sonja; Mörkl, Sabrina; Müller, Wolfram; Fürhapter-Rieger, Alfred; Oberascher, Andreas; Lehofer, Michael; Bieberger, Claudia; Wonisch, Willibald; Amouzadeh-Ghadikolai, Omid; Moser, Maximilian; Mangge, Harald; Zelzer, Sieglinde; et al.
Summary: Background & aims: Anorexia nervosa (AN) is a severe psychosomatic disease that seriously affects nutritional status. Therapeutic approaches primarily aim for rapid weight restoration by high caloric diets and activity restriction. This often promotes abdominal body fat gain, which potentially negatively influences the patient's compliance and increases the risk of relapse. This study focused on the evaluation of body weight and subcutaneous adipose tissue (SAT) in AN patients by novel approaches. Methods: The SAT of AN patients ( n  = 18, body mass index (BMI) 15.3 ± 1.3 kg/m 2 ) was determined by a highly accurate and reliable ultrasound method. The sum of SAT thicknesses of eight sites ( D INCL ) was calculated. Individual metabolic profiles were analyzed. The mass index (MI), which considers body proportions, was used in addition to BMI. Additional to the standard laboratory diagnostics, dermal carotenoids measured by resonance Raman spectroscopy, leptin, and oxidative stress indicators were determined. Results: The mean MI was 15.7 ± 1.4 kg/m 2 . The D INCL considerably differed between individuals with the same BMI. Half of the patients (Group 1) had low D INCL : 1.3–28.4 mm, and Group 2 showed values up to 58.2 mm (corresponding to approximately 6 kg SAT mass). The two group means differed by more than 300% ( P < 0.001). Accordingly, leptin levels significantly differed ( P < 0.001). Mean SAT thicknesses were significantly higher in Group 2 at all eight sites. The groups also significantly differed in two oxidative stress parameters: total antioxidative capacity, malondialdehyde-modified low density lipoprotein immunoglobulin M (MDA-LDL IgM), and in the carotenoid level. Conclusion: Half of the patients had sufficiently high fat mass, despite very low BMI. Consequently, their muscle (and other organ) masses must have been extremely low. Diagnostic criteria and treatment protocols for AN should consider each patient's body composition. In addition to dietary treatments, muscle training at low energy turnover rates may be essential for avoiding unnecessary body fat gain, better treatment results, and long-term recovery.